Risk Analysis of Flood Disasters in Junior High Schools of Surakarta, Indonesia - Grestina Melani; Yunus Aris Wibowo; Ratih Puspita Dewi (Universitas Muhammadiyah Surakarta, 2025)
Purpose: Flood disasters are one of the most frequent hydrometeorological hazards in Indonesia, significantly affecting the education sector, particularly schools located in flood-prone areas.Methodology: This study aims to analyze flood risk levels in junior high schools across Surakarta City by integrating hazard and vulnerability assessments using Geographic Information System (GIS) techniques. The hazard analysis employed parameters of slope, rainfall intensity, land use, and river proximity, which were weighted and overlaid to generate a flood hazard map. Vulnerability was assessed through physical (building structure, drainage, foundation, elevation, and materials) and social components (school community, teacher-staff gender ratio, and student gender ratio).Results: The results indicated that 40% of Surakarta's area fell under a high flood hazard zone, and most schools exhibit moderate levels of social and physical vulnerability. The flood risk matrix revealed that 43 schools (70%) fell into the high-risk category, 22 (28%) were moderate, and only 1 (2%) was low. The high-risk concentration corresponded with low-lying areas near the Bengawan Solo River Basin.Applications/Originality/Value: These findings emphasized the urgency of integrating Disaster Risk Reduction (DRR) into school-based programs such as Safe Schools from Disasters (SPAB) and improving physical infrastructure resilience. The outcomes of this study are expected to support local policy in flood mitigation planning for the education sector.